Study on the Movement and Distribution Patterns of Sand Particles in a Vane-Type Multiphase Pump - Chenwei Wang; Guangtai Shi; Yao Liu; Haigang Wen; Wenjuan Lv (Journal of Marine Science and Engineering)
In oilfield operations, produced fluids consist of complex mixtures including heavy oil, sand, and water. Variations in sand particle parameters and operational conditions can significantly impact the performance of multiphase pumps. To elucidate the movement patterns of sand particles within a vane-type multiphase pump, this study employs the Discrete Phase Model (DPM) to investigate the effects of different sand particle parameters and operational conditions on the internal flow characteristics. The study found that: sand particle diameter, flow rate, rotational speed, and oil content significantly influence the trajectories of the solid–liquid two-phase flow, the motion characteristics of sand particles, and the vortices in the liquid flow field. As sand particle diameter increases, their radial and axial momentum first rise and then decline. Both radial and axial momentum are positively correlated with sand concentration. An increase in flow rate, higher rotational speed, and lower oil content all lead to greater fluctuations in the radial momentum curve of sand particles inside the impeller. Larger sand particles are predominantly distributed near the inlet, while smaller particles are more concentrated at the outlet. Higher sand concentrations and non-spherical particles increase particle distribution within the flow passages, with the guide vane channels exhibiting the most pronounced accumulation—reaching a maximum concentration of 6260 kg/m3 due to elevated sand loading. Increasing flow rate, rotational speed, or oil content significantly reduces sand concentration in the flow channel, promoting more efficient particle transport. Conversely, lower inlet sand concentration, non-spherical particles, reduced flow rate, decreased rotational speed, and higher oil content all result in fewer large particles in the flow passage. The findings provide important guidance for improving the wear resistance of vane-type multiphase pumps.